SORPTION KINETICS OF IODINE IONS ON NEW IONITE BASED ON LOCAL RAW MATERIALS (Scientific journal of the Fergana State University, 2023)
By providing sulfocationite obtained on the basis of polyvinyl chloride, which is a local raw material, new ionizingmaterials containing both cation-exchange sulfogroup and anion-exchange amino groups were obtained. Absorptionkinetics and isotherms of iodine ions in aqueous solutions were calculated for the obtained ion-carrying material understatic conditions.